Higher body mass index is associated with reduced posterior default mode connectivity in older adults. Issue 7 (11th April 2017) - Beyer, Frauke; Kharabian Masouleh, Sharzhad; Huntenburg, Julia M.; Lampe, Leonie; Luck, Tobias; Riedel‐Heller, Steffi G; Loeffler, Markus; Schroeter, Matthias L.; Stumvoll, Michael; Villringer, Arno; Witte, A. Veronica
Abstract: Obesity is a complex neurobehavioral disorder that has been linked to changes in brain structure and function. However, the impact of obesity on functional connectivity and cognition in aging humans is largely unknown. Therefore, the association of body mass index (BMI), resting‐state network connectivity, and cognitive performance in 712 healthy, well‐characterized older adults of the Leipzig Research Center for Civilization Diseases (LIFE) cohort (60–80 years old, mean BMI 27.6 kg/m 2 ± 4.2 SD, main sample: n = 521, replication sample: n = 191) was determined. Statistical analyses included a multivariate model selection approach followed by univariate analyses to adjust for possible confounders. Results showed that a higher BMI was significantly associated with lower default mode functional connectivity in the posterior cingulate cortex and precuneus. The effect remained stable after controlling for age, sex, head motion, registration quality, cardiovascular, and genetic factors as well as in replication analyses. Lower functional connectivity in BMI‐associated areas correlated with worse executive function. In addition, higher BMI correlated with stronger head motion. Using 3T neuroimaging in a large cohort of healthy older adults, independent negative associations of obesity and functional connectivity in the posterior default mode network were observed. In addition, a subtle link between lower resting‐state connectivity in BMI‐associated regions and cognitive function was found. The findings might indicate that obesity is associated with patterns of decreased default mode connectivity similar to those seen in populations at risk for Alzheimer's disease. Hum Brain Mapp 38:3502–3515, 2017 . ©2017 Wiley Periodicals, Inc.